1992
DOI: 10.1002/bem.2250130708
|View full text |Cite
|
Sign up to set email alerts
|

Some engineering models for interactions of electric and magnetic fields with biological systems

Abstract: The objective of this paper is to review some of the fundamental mechanisms for the interaction of electric and magnetic fields with biological systems at variable levels of field strengths and to examine several possible ways by which weak fields may influence these systems. We begin with a review of the basic equations by which electric or magnetic fields interact with biological fluids and follow it with a look at the effects of inserting a simple cell membrane. The initial starting points are the force equ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

1992
1992
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…Thus, the cellular membrane potential should be capable of being affected by the magnetic field because the moving charges are subjected to the Lorentz force under a magnetostatic field. As mentioned above, the ordered alignment of magnetic moments can yield a localized magnetic field, which can further influence the transmembrane streaming of some ions, especially Ca 2+ [32,33]. Ca 2+ is an important physiological transmitter and Ca element is also directly relative with formation of bone so that the presence of magnetism or magnetic materials can enhance the growth of osteoblasts (including the viability of cells).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the cellular membrane potential should be capable of being affected by the magnetic field because the moving charges are subjected to the Lorentz force under a magnetostatic field. As mentioned above, the ordered alignment of magnetic moments can yield a localized magnetic field, which can further influence the transmembrane streaming of some ions, especially Ca 2+ [32,33]. Ca 2+ is an important physiological transmitter and Ca element is also directly relative with formation of bone so that the presence of magnetism or magnetic materials can enhance the growth of osteoblasts (including the viability of cells).…”
Section: Resultsmentioning
confidence: 99%
“…EFs can affect cellular processes, including microfilament reorganization, proliferation, differentiation, and apoptosis, by causing a redistribution of charged cell-surface receptors, altering cell shape, and increasing the release of signaling molecules such as intracellular calcium (Barnes, 1992;Cho et al, 1994Cho et al, , 1996Haddad et al, 2007;Titushkin and Cho, 2009). Several studies have reported the effect of exogenous EFs applied to various stem cells in vitro.…”
Section: Introductionmentioning
confidence: 99%
“…Many of these influence charged molecules associated with membranes (reviewed by Barnes, 1992). These effects include the exertion of force on moving charge carriers; alteration of the trans-membrane diffusion rate; distortion of bond angles which in turn affects protein binding and macromolecular synthesis; and change in the rate of proton tunnelling between DNA nucleotide bases (Barnothy, association surface architecture and microtubule network association may be explained by either one being causal upon the other, or that they have a common causality residing in a morphogenetic field.…”
Section: Effect Of Applied Magnetic Field On Uncleaved Eggsmentioning
confidence: 99%